Characteristics of vacuum solenoid valves in case of various malfunctions. Issue 1 (December 2020) - Stoyanov, Stoyan; Mihaylov, Veselin; Ivanov, Zdravko
Abstract: Vacuum solenoid valves are used to control actuators, in most cases connected with the emission system. In general, the diagnosis of modern cars is difficult due to the large number of elements and the fact that usually they gradually change their characteristics but remain operational. This is especially important for elements without feedback. The purpose of this research is to determine characteristics of faulty valves, which could be useful in diagnostics process. The results show change of valve characteristics at some of the most common problems during long term operation of the vehicle.